2023
DOI: 10.1101/2023.01.31.525875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perforin-2 is a pore-forming effector of endocytic escape in cross-presenting dendritic cells

Abstract: During initiation of antiviral and antitumour T cell-mediated immune responses, dendritic cells (DCs) cross-present exogenous antigens on MHC class I. Cross-presentation relies on the unique leakiness of endocytic compartments in DCs, whereby internalised proteins escape into the cytosol for proteasome-mediated generation of MHC I-binding peptides. Given that type 1 conventional DCs excel at cross-presentation, we searched for cell-type specific effectors of endocytic escape. We devised an escape assay suitabl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…First, while XP has been observed in a variety of APCs in vitro, only cDC1s appear to serve a non-redundant role in cross-priming to many types of viruses and tumours in vivo 1,9,10,[80][81][82][83] . Second, the XP of cell-associated antigens by cDC1s often involves the delivery of antigens to the cytosol 11,20,21,23,28,34,50,63 . In line with this, several groups have recently shown that, in cDC1s, endocytic organelles, including phagosomes, appear to be "damage prone" and to display signs of breached or ruptured membranes 11,23,27,28,65 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, while XP has been observed in a variety of APCs in vitro, only cDC1s appear to serve a non-redundant role in cross-priming to many types of viruses and tumours in vivo 1,9,10,[80][81][82][83] . Second, the XP of cell-associated antigens by cDC1s often involves the delivery of antigens to the cytosol 11,20,21,23,28,34,50,63 . In line with this, several groups have recently shown that, in cDC1s, endocytic organelles, including phagosomes, appear to be "damage prone" and to display signs of breached or ruptured membranes 11,23,27,28,65 .…”
Section: Discussionmentioning
confidence: 99%
“…MuTuDCs are frequently used to study XP, have a similar proteomic profile to primary cDC1s in vivo, and have shown evidence of phagosomal rupture 11,23,[28][29][30][31][32][33][34] . We first treated MuTuDCs with poly(I:C), which can trigger TLR3 that is particularly abundant on cDC1s and favours enhanced cross-priming 31,[35][36][37][38][39][40][41][42] .…”
Section: Poly(i:c) Leads To a Greater Incidence Of Phagosomal Membran...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the transporters SLC15A3 and SLC15A4 mediate MDP efflux from phagolysosomes in macrophages and dendritic cells to promote NOD2 activation 63,65,179 (Figure 3). Additionally, the pore‐forming protein perforin 2 mediates export of ingested antigens in dendritic cells to promote cross‐presentation 194 . It is likely that other transporters and channels support innate immune signaling in phagocytes, but this requires further study.…”
Section: Consequences Of Solute Efflux: Signaling and Metabolismmentioning
confidence: 99%
“…Additionally, the pore-forming protein perforin 2 mediates export of ingested antigens in dendritic cells to promote cross-presentation. 194 It is likely that other transporters and channels support innate immune signaling in phagocytes, but this requires further study.…”
Section: Whereas Membrane Rupture Releases Phagosomal Contentsmentioning
confidence: 99%